Microbiome in the ice-ice disease of the farmed red algae Kappaphycus alvarezii and degradation of extracted food carrageenan. (August 2021) - Mohammed Riyaz, S.U.; Inbakandan, D.; Manikandan, D.; Bhavadharani, P.; Elson, J.; Srinivasa Prabhu, N.; Stalin Dhas, T.; Nalini, S.; Bavani Latha, M.; Simal-Gandara, J.
Abstract: Kappaphycus alvarezii, a macroalgae which produces a strong and rigid gel like substance called κ-carrageenan. The development of ice-ice disease in the K. alvarezii seaweed has considerable consequences for the carrageenan business. Effect of ice-ice diseases on carrageenan quality in relation to healthy K. alvarezii was examined completely by different analytical methods like UV-Spectrometry, FTIR, 1 H NMR, HPLC, GC-MS. Histological studies like sectioning of ice - ice diseased tissue showed variations in structure of the polysaccharides, which also confirms the association of pathogens in K. alvarezii . Analysis of carrageenan degradation was done based on high-throughput Illumina sequencing of the V3 –V4 region of the 16S rRNA gene, since the assessment of microbiome plays a major role in assessing the health of the seaweed. This region provides ample information for taxonomic classification of microbial communities from specimens associated with microbiome studies. Carrageenase from bacteria for the disease degrades the carrageenan.